(untitled) (Journal of Parents and Teachers, 2026)
Through the relationship between Bruno and his grandson, inspired by José Luis Sampedro’s La Sonrisa Etrusca (The Etruscan Smile), he shows that the birth of his grandson transforms his life, his feelings and the way he sees the world. He also highlights the feelings that exist in intergenerational bonds. He emphasises the idea that grandparents and grandchildren educate each other.